Development of socioscientific issues-based e-module on environmental change topic - Diyyan Marneli; Febri Yulia Susanti (Jurnal Biolokus: Jurnal Penelitian Pendidikan Biologi dan Biologi, 2022)
This research background was the limitation of online learning resource and lack of e-module in learning process especially in using socioscientific issues approach. Moreover, the teaching material was less attractive and comprehensive that causes lack of students learning interest. This study aimed to produce e-module based on socioscientific issues in environmental change topic for senior high school students grade X. The research was conducted in SMAN 1 Padang Ganting in even semester 2021-2022. 4D (define, design, development and diseminate) model used to develop the e-module. This research result was the e-module produced have 83% in validity and categorized as very valid, 88% in practicality based on teacher’s questionnaire and 84% based on student’s questionnaire which categorized very practical. This suggets that e-module developed meet all aspects of a research development and in accordance with the characteristics of a teaching materials. It can be concluded that the socioscientific issues-based e-module developed was valid and practice for biology learning in senior high school.